2018
DOI: 10.1002/eji.201847477
|View full text |Cite
|
Sign up to set email alerts
|

Association between levels of synovial anti‐citrullinated peptide antibodies and neutrophil response in patients with rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is characterized by the presence of anti-citrullinated peptide antibodies (ACPAs) and neutrophils infiltrating the synovial fluid (SF) of the affected joints. The aim of this work was to analyze whether the presence of ACPAs in SF is associated with neutrophil infiltration and with their phenotype in the inflamed joints of RA patients. We found that in the presence of ACPAs, the number of synovial neutrophils correlated with severe disease activity. The SF were divided according to sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…One limitation of our study is the use of an in vitro model of RA to validate our transcriptomics data. Whilst the incubation of healthy control neutrophils in RA SF is a widely used model of the disease (48,(70)(71)(72), future studies should focus on validating the RA SF neutrophil phenotype using ex vivo RA SF neutrophils. There have been a number of reports on the properties of RA SF neutrophils and in general these show an activated phenotype, in terms of surface receptor expression, ROS production and apoptosis (see Introduction).…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of our study is the use of an in vitro model of RA to validate our transcriptomics data. Whilst the incubation of healthy control neutrophils in RA SF is a widely used model of the disease (48,(70)(71)(72), future studies should focus on validating the RA SF neutrophil phenotype using ex vivo RA SF neutrophils. There have been a number of reports on the properties of RA SF neutrophils and in general these show an activated phenotype, in terms of surface receptor expression, ROS production and apoptosis (see Introduction).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the homogeneity of neutrophil population has become increasingly questionable, with detection of neutrophils exhibiting distinct functions and profiles leading to the concept of different subsets . Several studies have indeed demonstrated that alternatively activated and/or HEV‐recruited neutrophils can regulate the adaptive immune response by inhibiting B and T lymphocyte responses, in particular in the context of antibody production during vaccination challenge and infections . Whilst the mechanisms associated with such functions are not fully understood, neutrophil suppressive properties on T lymphocyte activities involve the release of reactive oxygen species, NO or Arginase 1 (Arg‐1) in close vicinity of targeted lymphocytes .…”
Section: Neutrophil Regulation Of Lymphocyte Functionsmentioning
confidence: 99%
“…Solid evidence exists that supports the important role of NETs in the pathogenesis of RA [8, 9, 13, 20, 73]. NET formation has been identified as a link between the innate and adaptive immune responses in autoimmunity.…”
Section: The Role Of Nets In the Pathogenesis Of Ramentioning
confidence: 99%
“…Sera and immunoglobulin fractions from RA patients with high levels of ACPA or RF significantly enhanced NETosis. In vitro incubation of neutrophils with ACPA high synovial fluid results in increased ROS production and extracellular DNA release compared to neutrophils incubated with ACPA-negative synovial fluid [20].…”
Section: The Role Of Nets In the Pathogenesis Of Ramentioning
confidence: 99%